Needs Analysis in ESP and their Relationship with English for Civil Engineering Students - Endah P Haryono (Politeknik Negeri Manado, 2020)
There is a very close interdependent relationship between English for Specific Purpose (ESP) and Needs Analysis (wants / interests analysis). ESP is an approach in teaching English based on the students’ needs, while Needs analysis is an approach used to find out the full and accurate information about the needs of students in learning English. This article discusses about the important understanding of ESP and Needs analysis in language teaching, the history and development of the two disciplines as well as the relationship between need analysis and ESP in which all the issues give very essential contributions to the process of language learning especially in Teaching English for Civil Engineering students. The strongly advantage implication provided by those principles is; it can help designers and teachers of civil engineering to be able to identify all kinds of needs such as, methods of learning, learning materials, language content and assessment which are required and desired by the learners particularly civil engineering practitioners.